2019
DOI: 10.1108/hff-05-2019-0409
|View full text |Cite
|
Sign up to set email alerts
|

LBM simulation of piezo fan in square enclosure

Abstract: Purpose This paper aims to investigate the use of a piezo fan in an enclosure on wall heat transfer and thermal boundary layer profile in constant wall temperature situation. Design/methodology/approach The governing partial differential equations of mass, momentum and energy in addition to boundary conditions are solved by lattice Boltzmann method. The problem is solved numerically using D2Q9 population's model and Bhatnagar–Gross–Krook collision model with a code written in MATLAB. Findings The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Various examinations have demonstrated that the grid Boltzmann technique is successful in contemplating the convection heat move under different field powers. References [16][17][18][19][20][21][22][23][24][25][26][27][28][29] in constrained convection, results uncovered that temperature inclination decreases with the ascent of Rayleigh number. In normal convection, the normal Nusselt number increments with the expansion of Rayleigh number and the lessening of Hartmann number.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Various examinations have demonstrated that the grid Boltzmann technique is successful in contemplating the convection heat move under different field powers. References [16][17][18][19][20][21][22][23][24][25][26][27][28][29] in constrained convection, results uncovered that temperature inclination decreases with the ascent of Rayleigh number. In normal convection, the normal Nusselt number increments with the expansion of Rayleigh number and the lessening of Hartmann number.…”
Section: Introductionmentioning
confidence: 93%
“…LBM compared to MRT, has better accuracy, convergence, and stability. Jamalabadi [22] examined the warmth dispersal impact of ferrofluid regular convection in a slanted depression under the attractive field. Different Rayleigh numbers and slanted edges were considered, and slanted edge at 0 degrees and Rayleigh number at 10 4 ended up being the best circumstance for heat scattering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The produced fluid flow is the highest at zero deflection of the beam. The minimum is reached at the beam maximum amplitude [9]. A piezoelectric oscillating cantilever fan is a reliable, highly energy efficient, silent, reliable, simple constructed, inexpensive and has a long lifetime [10].…”
Section: Piezoelectric Oscillating Cantilever Fanmentioning
confidence: 99%
“…Yu et al [36] and Sun et al [37] performed classical nonlinear works on sloshing while the nonlinearity refers to the fluid part. Jamalabadi [38,39] solved the FSI problem in analytical sloshing, sloshing with the improved boundary layer approximation [40], sloshing with finite element [41,42], LBM [43], and sloshing with SPH method [44]. In many of studies a linear elastic model is adopted for solid part and focus of accuracy is on fluid section [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%